HIPAA Program Reference Handbook, The - Leo, Ross (CRC Press, 2009)
* Presents practical recommendations for reaching and maintaining HIPAA compliance * Contains contributed articles from HIPAA experts-consultants, employees of covered entities, and members of the standards bodies-who have worked first-hand with the standards and requirements * Covers HIPAA program fundamentals including Due Diligence, workforce education, issues analysis, and internal control structures and requirements * Addresses the standards of performance, execution, and due care that must be met to establish compliance